Neutrophils engage the kallikrein‐kinin system to open up the endothelial barrier in acute inflammation. Issue 2 (3rd October 2018) - Kenne, Ellinor; Rasmuson, Joel; Renné, Thomas; Vieira, Monica L.; Müller-Esterl, Werner; Herwald, Heiko; Lindbom, Lennart
ABSTRACT: Neutrophil recruitment and plasma exudation are key elements in the immune response to injury or infection. Activated neutrophils stimulate opening of the endothelial barrier; however, the underlying mechanisms have remained largely unknown. In this study, we identified a pivotal role of the proinflammatory kallikrein‐kinin system and consequent formation of bradykinin in neutrophil‐evoked vascular leak. In mouse and hamster models of acute inflammation, inhibitors of bradykinin generation, and signaling markedly reduced plasma exudation in response to chemoattractant activation of neutrophils. The neutrophil‐driven leak was likewise suppressed in mice deficient in either the bradykinin B2 receptor or factor XII (initiator of the kallikrein‐kinin system). In human endothelial cell monolayers, material secreted from activated neutrophils induced cytoskeletal rearrangement, leading to paracellular gap formation in a bradykinin‐dependent manner. As a mechanistic basis, we found that a neutrophil‐derived heparin‐binding protein (HBP/azurocidin) displaced the bradykinin precursor high‐molecular‐weight kininogen from endothelial cells, thereby enabling proteolytic processing of kininogen into bradykinin by neutrophil and plasma proteases. These data provide novel insight into the signaling pathway by which neutrophils open up the endothelial barrier and identify the kallikrein‐kinin system as a target for therapeutic interventions in acute inflammatory reactions.—Kenne, E., Rasmuson, J., Renné, T., Vieira, M. L., Müller‐Esterl, W., Herwald, H., Lindbom, L. Neutrophils engage the kallikrein‐kinin system to open up the endothelial barrier in acute inflammation. FASEB J. 33, 2599–2609 (2019). www.fasebj.org